Pengaruh Pemberian Bahan Organik yang Diperkaya Mikroba Bambu Terhadap Pertumbuhan dan Produksi Kangkung Darat (Ipomoea reptans) - Zahanis Zahanis; Widodo Haryoko; Megi Martavia (Jurnal Embrio, 2018)
Experiment have been done in village Aro Kandikia Nagari Gaduik Kecamatan Tilatang Kamang Kabupaten Agam of februari- april 2013, the purpose of this research to get measure organic matter enriched microbes bamboo proper to growth and the production of convolvulus land. Complete random design , in the provision of organic matter bamboo microbes that is repeated three times .The given consisting of 0 ( mo ) , volume of ) 0.25 ( , 0.5 meters , 1 ( m3 ) , 1.25 ( m4 ) , 1.5 ( (m5 ) . The outcome of the experiment shows that growth and the production of plants convolvulus land the highest is in the provision of 1 kg per a plot to the production of 78 g per a clump or equivalent to 15,4 ton / ha , while production the lowest in the provision of 0 kg namely 66 g per a clump or equivalent to 13.2 ton / ha .